Long-Term Performance of Electrodes Based on Vinyl Acetate Homo-Polymer Binder - Paolo Prosini, Pier; Di Carli, Mariasole; Della Seta, Livia; Carewska, Maria; Fuso Nerini, Ivan (Journal of Research Updates in Polymer Science, 2017)
In this work we propose the use of a hydro-dispersible polymer such as the poly vinyl acetate as a binder for the production of electrodes for lithium-ion batteries. To increase the film forming properties of the polymer the poly vinyl was added with triacetin that acts as a plasticizer. The electrochemical stability of the polymer was tested by a polarizing electrode, formed by mixing the polymer with carbon. Subsequently, an electrode tape was prepared by using LiNi0.5Mn1.5O4 as the active material and characterized by SEM, EDS and TGA. Lithium metal cells were assembled and tested to evaluate specific capacity, power and energy density at various discharge rates. The cycle life of the cell was evaluated by galvanostatic charge/discharge cycles. The tests showed that the electrodes prepared with PVA plasticized with triacetin have very good electrochemical performance in terms of capacity retention as a function of the discharge rate and the cycle number. Our work demonstrates that the use of triacetin to plasticize the PVA allows to increase the electrochemical stability of the electrode likely due to an improvement of the slurry filmability. The proposed method could represent a promising technology for the production of long-term performance lithium batteries.